2023
DOI: 10.3390/ijms242015233
|View full text |Cite
|
Sign up to set email alerts
|

Expression of PD-1 and PD-L1 in Endometrial Cancer: Molecular and Clinical Significance

Mohd Nazzary Mamat @ Yusof,
Kah Teik Chew,
Nirmala Chandralega Kampan
et al.

Abstract: The landscape of diagnosing and treating endometrial cancer is undergoing a profound transformation due to the integration of molecular analysis and innovative therapeutic approaches. For several decades, the cornerstone treatments for endometrial cancer have included surgical resection, cytotoxic chemotherapy, hormonal therapy, and radiation therapy. However, in recent years, the concept of personalised medicine has gained momentum, reshaping the way clinicians approach cancer treatment. Tailoring treatments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 125 publications
0
1
0
Order By: Relevance
“…Studies indicate that ectopic endometrial tissue exhibits heightened PD-L1 expression, which may serve as a defense mechanism against immune attacks. This overexpression inhibits T cell activation within ectopic tissues, reducing their cytotoxic response and thereby decreasing the elimination of pathological tissue, allowing for its continued proliferation [ 13 , 14 , 15 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies indicate that ectopic endometrial tissue exhibits heightened PD-L1 expression, which may serve as a defense mechanism against immune attacks. This overexpression inhibits T cell activation within ectopic tissues, reducing their cytotoxic response and thereby decreasing the elimination of pathological tissue, allowing for its continued proliferation [ 13 , 14 , 15 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…This upregulation can inhibit the cytotoxic activity of T and B lymphocytes, reducing their effectiveness in eliminating ectopic endometrial tissue. However, the extent and precise mechanisms by which PD-1 and PD-L1 contribute to immune evasion in endometriosis remain unclear, forming the basis for further investigation in this study [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, additional investigation is warranted to elucidate the immune microenvironment and specific immune suppression pathways in POLE-mut EC, which could potentially lead to novel therapeutic interventions for advanced-stage POLE-mutant tumors. [50][51][52] Detection and Alternative Testing Methods for Pathogenic POLE Mutations…”
Section: "Multiple-classifier" Endometrial Cancer With Diverse Charac...mentioning
confidence: 99%
“…It has already been indicated that cancers with MMR deficiency, including EC, may be susceptible to programmed death 1/programmed death-ligand 1 (PD-L1) inhibitors [ 106 , 118 , 119 , 120 , 121 ]. PD-L1 expression on tumor and/or immune cells is considered a predictive factor of immunotherapy efficacy in, e.g., non-small-cell lung cancer patients [ 121 , 122 ]. It was shown that PD-L1 expression is also frequently high in EC patients [ 123 , 124 ].…”
Section: Ec Treatmentmentioning
confidence: 99%